El tránsito Aragoniense-Vallesiense en el área de Daroca-Nombrevilla (Zaragoza, España) - autor, Sin (Coloquios de Paleontología, 2003)
Despite the extensive continental fossil record from the Spanish Miocene, few localities from deposits covering the Aragonian- Vallesian boundary are known. During the last few years new sampling has been carried out around Daroca (Zaragoza, Spain) in order to complete the information of that interval. In addition, lithostratigraphic and sedimentological studies as well as magnetostratigraphic sampling have been done. The results of all these studies allow to recognise a stratigrafic section that includes fifteen mammal fossil localities (of which nine are new) completing our knowledge of the fossil record of the upper Aragonian-lower Vallesian.